Identifying Cultural Values of the Narrative Texts in an English Textbook for Tenth Grade of Senior High School - Urip Sulistiyo; Kaspul Anwar; Gemila Lestari; Desi Afriani; Widya Kartika; Retno Wulan (Soegijapranata Catholic University, 2020)
Many English teachers assumed that culture cannot be separated from English learning. This paper aimed to investigate the cultural values of the narrative texts in English textbook for grade tenth of senior high school. The data of the research were collected from narrative reading passage in English textbook for senior high school entitled “Bahasa Inggris”, English textbook Curriculum 2013 (henceforth, K13) published by The Ministry of Education of Republic of Indonesia. To reveal what culture values represented in the narrative reading passage in the textbook, the cultural values were categorized into several source cultures such as visual representation of the cultures, and the objectives of the lesson related to cultural values in narrative texts. Moreover, the findings of this research discovered that there were three cultural values identified in the narrative reading passages in the textbook such as respect for the right indigenous people, finding peace and nature and with all forms of life, and appreciation of cultural products.